2022
DOI: 10.23969/jrak.v14i1.4932
|View full text |Cite
|
Sign up to set email alerts
|

Fraud in Accounting: Surveys on Hotels in Bandung

Abstract: This research aims at determining the Accounting fraud that deliberated violation of the law which involved embezzlement, fraud, abuse of trust, etc by making inappropriate financial reports that can mislead decisionmakers and link to the undesirable financial frauds. This research was conducted by analyzing and testing the impact of the role of internal audit, the effectiveness of internal control, and unethical behaviour on accounting fraud at several stars hotels in Bandung. The research method used primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The results of this research were in line with the results of research by Fitriyah & Novita on State-Owned Enterprises companies listed on the Indonesia Stock Exchange, where opportunity had a significant influence on fraudulent financial statements (Fitriyah & Novita, 2021). Conversely, other studies had shown that there was no significant effect of opportunity on financial reporting fraud (Julianty et al, 2022, Syafira & Cahyaningsih, 2022.…”
Section: Introductionsupporting
confidence: 87%
“…The results of this research were in line with the results of research by Fitriyah & Novita on State-Owned Enterprises companies listed on the Indonesia Stock Exchange, where opportunity had a significant influence on fraudulent financial statements (Fitriyah & Novita, 2021). Conversely, other studies had shown that there was no significant effect of opportunity on financial reporting fraud (Julianty et al, 2022, Syafira & Cahyaningsih, 2022.…”
Section: Introductionsupporting
confidence: 87%
“…This study shows accounting students argue that company management is responsible for accounting scandals. Furthermore, (Julianty et al, 2022) stated that management or trusted position may also involved in a fraud action. Their hope is that accountants can implement ethical principles to avoid future business scandals.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted on corporate fraud and resulted in a theoretical framework (Purwati et al, 2022). Fraud cases in Indonesia continue to increase from year to year and occur in various sectors, including education (Julianty et al, 2022;Pura & Sufiati, 2014;Savitri et al, 2022). This sector should be completely free from fraud, especially corruption.…”
Section: Introductionmentioning
confidence: 99%